On Building the American and the European Empires - Josep M. Colomer (London School of Economics and Political Science (LSE), European Institute, 2010)
The processes of building the United States of America (USA) during the nineteenth century and the European Union (EU) since mid-twentieth century are among the major claims for the possibility of a vast, 'imperial'-size political unit based on democratic principles. The crucial period for the consolidation of the USA was between the Civil War and the First World War, when it established clear territorial limits and completed its internal institutionalization as a federal democratic union. While the EU has achieved higher levels of economic integration on some issues than the USA did one hundred years ago, it still recognizes a number of additional candidates to become member-states and has not attained a stable constitutional framework. As it was the case for the USA about a century ago, for the current European Union putting an end to the process of territorial expansion and fixing neat external frontiers seems to be a necessary condition to achieve internal institutional stability and robust federal formulas.
Keywords: 330